Metafisika Hikmah dan Implikasinya dalam Pendidikan Islam - Muharam, Asep; Kemala, Ratu; Juwita, Dea Intan (Kaipi: Kumpulan Artikel Ilmiah Pendidikan Islam, 2024)
This study aims to explore the meanings of "hikmah" (wisdom) in the Qur'an and investigate its implications for Islamic education, considering the Sapir-Whorf theory on the influence of language structure on thought structure. The methodology involves textual analysis of Qur'anic sources and classical exegesis, using a qualitative approach to delve into the meanings embedded in the term "hikmah." The findings identify seven main meanings of hikmah in the Qur'an: first, preventive measures aimed at preventing negative thoughts and actions; second, practical lessons serving as life guidelines; third, understanding that links knowledge and action as a form of practical application; fourth, prophetic gift reflecting hikmah as part of divine revelation; fifth, Qur'anic interpretation relating hikmah to deep understanding of the sacred text; sixth, beneficial knowledge applied for good; and seventh, wise speech reflecting correct and precise communication. The study concludes that hikmah in the Qur'an embodies a combination of knowledge, understanding, and practical application in daily life. The implications suggest that integrating hikmah values into Islamic education can enrich the curriculum with a focus on character development and practical application. Additionally, the study supports the Sapir-Whorf theory by showing how language understanding affects educational practices and character formation, highlighting that language structure can influence thinking and learning processes.